ANALISIS KEKUATAN KOLOM BETON BERTULANG YANG DIPERKUAT DENGAN METODE CONCRETE JACKETING - Aulia Rahman; Samsunan Samsunan; Meidia Refiyanni; Ruhdi Faisal; Nina Shaskia; Singgih Prabowo Soksen (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
The December 2004 earthquake and tsunami in Aceh still have an impact on buildings. The Korem 012/TU Mess Building Ujong Karang Meulaboh, Aceh Province is one of the buildings affected. Structural strengthening is required by comparing the strength of the existing building with the strength of the planned building. The structural strengthening method used in this research is the concrete jacketing construction method. This study aims to evaluate and compare how much the column capacity, internal force and floor deviation before and after the column is reinforced with the concrete jacketing method. There were several loads assigned to the structure, i.e., dead, live, wind, and earthquake loads. As for the analysis, the load combinations were considered. The research method used is the graphical and tabular analysis method analyzed using SAP2000 Version 22 software by making 2 existing models and plans, the reinforcement system is carried out on the 1st floor columns totaling 14 columns. This research resulted in the maximum moment, maximum shear force, and maximum axial force before and after the columns were reinforced with a percentage increase of 31%, 23%, 35% respectively. The maximum deviation between floors in the "Y" direction that occurred in the columns before reinforcement was 9.686 mm. From the analysis, it can be seen that the column capacity after strengthening with jacketing method is 3257.30 kN compared to 1299.54 kN before strengthening, so there is a difference of 1957.76 kN increase in column capacity.